Cloud-Based API Gateways for Seamless Multi-Platform Integration - Ravinder Ramidi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud-based API gateways offer vital solutions for integrating systems across diverse environments in today's multi-cloud landscape. These gateways provide centralized control for managing, securing, and optimizing API traffic across distributed systems, addressing challenges organizations face when operating across multiple platforms. Key gateway functions include request routing, protocol translation, authentication, rate limiting, caching, lifecycle management, and monitoring capabilities. Major providers—AWS, Azure, and Google Cloud—offer solutions with unique strengths suitable for different business scenarios. Effective integration patterns for customer data, payment processing, and analytics implementations complement optimization techniques spanning performance, security, and fault tolerance. Advanced approaches including serverless functions, microservices patterns, and edge computing enhancements receive particular attention, while a phased implementation roadmap ensures successful adoption across enterprises seeking to modernize their integration infrastructure.
Keywords: Multi-cloud integration; API gateway architecture; Microservices patterns; Edge computing; Security optimization